Atribuições, competências, trabalho e identidade: uma aproximação aos significados produzidos pelos assistentes sociais no percurso do exercício profissional - Souza, Bianca Ribeiro de (2013)
Considering Articles 4 and 5 of Law 8.662/1993 (Social Work Professional Regulation), this paper aims at problematizing social workers understanding of their professions in several socio-occupational places, with predominance of those which do not provide direct customers assistance. Specific objectives are to: historicize the process of professional regulation; analyze attributions and competencies based on professional legislation; and assess development of professional identity by exercising these attributions and competencies. It is important to apprehend the way social workers have been conducting their works considering enlargement of socio-occupational places and changing demands addressed to Social Work since decentralization of public policies. Moreover, discussions on identity in relation to performance of these attributions and competencies prove to be a tool to strengthen professionals in the face of managing daily difficulties that arise in work places. We adopted a qualitative approach involving semi-structured interviews. Participants were 06 social workers: 1 counselor/advisor; 1 manager of National Social Assistance Policy (Specialized Social Protection); 1 interdisciplinary team coordinator of São Paulo State Public Prosecutor; 1 social worker included in Public Health Surveillance Center team; 1 coordinator of Reference Center of Social Assistance; 1 social worker included in São Paulo State Public Defender Service. Narrative analysis was based on Marxist theoretical perspective, which considers Social Work as work. Thus, grounded on participants´ speeches transcripts, we operationalized 04 categories of narrative analysis: professional attributions and competencies; professional work; concept of profession; and identity. The categories appeared during the participants´ narratives and were suitable to reach our research objectives